"Liking" and "Take Away" Preferences for Mexican Consumers: Cross‐Cultural Comparison with Thais for Psychological Style. Issue 1 (5th February 2015) - Calderón, Eduardo; Angulo, Ofelia; O'Mahony, Michael; Wichchukit, Sukanya
Abstract There are reports in the literature that for paired preference tests with a "No Preference" option, Mexican consumers have a lower frequency of "No Preference" responses than Thais. For a more exact comparison of these differences in psychophysical style, Mexican consumers performed preference tests using, as closely as possible, the experimental method used in the Thai experiments. Comparison between this study and the Thai studies confirmed the differences in "No Preference" frequencies, suggesting a systematic cross‐cultural effect of psychophysical style. Mexican consumers also performed "take away" preferences for the first time and their results corresponded more with the regular paired preference tests than was the case with Thais. Practical Applications Paired preference tests are a subset of measures available for consumer acceptance. Considering the importance of efforts to predict consumer acceptance, it is essential to understand the variables and biases associated with such tests. Because cross‐cultural measurement is becoming more critical in a globalized world, any systematic cross‐cultural differences should not be ignored. The present study investigated a possible stable cross‐cultural difference with the use of paired preference tests between two potential markets. For companies that sell their products in a variety of countries, such differences will need to be taken into account when interpreting paired preference data and accordingly are worthy of investigation.